The Role of Community Police Officer (Bhabinkamtibmas) in Suppressing the Theft under Aggravating Circumstances Rate the Purwakarta Police Department - Panjaitan, Andreas (Advances in Police Science Research Journal, 2020)
The focus of the research conducted by this writer is on the role of Community Police Officer (Bhabinkamtibmas) in suppressing the number of thefts by weighting the Purwakarta Police. The focus of this study is deemed important because the Purwakarta Police Service has not played an active role in suppressing the theft under aggravating circumstances rate it at the Purwakarta Police. The problems raised in this researchare: (1) Handling Bhabinkamtibmas in Door to Door activities to suppress the theft under aggravating circumstances, (2) Factors that hinder the role of Bhabinkamtibmas in the implementation of suppressing theft under aggravating circumstances rates. To analyze these existing problems, researchers used a qualitative approach with field methods and research as a whole (holistic). The use of a conceptual framework in the form of theories and concepts is used as a knife of analysis by researchers in answering the predetermined problem formulations. The theory and concepts used by the researcher are the crime prevention theory, the concept of Bhabinkamtibmas in the Bhabinkamtibmas Smart Book. The findings during this study are (1) Inhibiting factors that make the role of community service providers also have no visible impact in suppressing Curat. (2) Inadequate budget causes Door to Door activities cannot be carried out optimally. (3) Implementation of very rare activities that make the public also cannot submit complaints to the bhabinkamtibmas because Door to Door activities are not well planned.